2021
DOI: 10.1371/journal.pone.0253328
|View full text |Cite
|
Sign up to set email alerts
|

HSP70-mediated neuroprotection by combined treatment of valproic acid with hypothermia in a rat asphyxial cardiac arrest model

Abstract: It has been reported that valproic acid (VPA) combined with therapeutic hypothermia can improve survival and neurologic outcomes in a rat asphyxial cardiac arrest model. However, neuroprotective mechanisms of such combined treatment of valproic acid with hypothermia remains unclear. We hypothesized that epigenetic regulation of HSP70 by histone acetylation could increase HSP70-mediated neuroprotection suppressed under hypothermia. Male Sprague-Dawley rats that achieved return of spontaneous circulation (ROSC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
(92 reference statements)
0
8
0
Order By: Relevance
“…The cellular response to heat-induced stress is also manifested by an increased expression of heat shock proteins (Hsps) or chaperones. Among these, Hsp70 and Hsp90 display a neuroprotection effect in ischemic stroke models [12,14]. Although studies focusing on the link between hypothermia and chaperone expression are relatively limited, molecular tests showed that Hsp70 overexpression is associated with increased neuronal resistance and faster regeneration following hypoxia-induced cerebral cortical injuries [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cellular response to heat-induced stress is also manifested by an increased expression of heat shock proteins (Hsps) or chaperones. Among these, Hsp70 and Hsp90 display a neuroprotection effect in ischemic stroke models [12,14]. Although studies focusing on the link between hypothermia and chaperone expression are relatively limited, molecular tests showed that Hsp70 overexpression is associated with increased neuronal resistance and faster regeneration following hypoxia-induced cerebral cortical injuries [23].…”
Section: Discussionmentioning
confidence: 99%
“…Its role in cerebral protection and postlesional repair has recently been recognized, being recommended as one of the most specific astrocyte markers according to investigations of its association with depression, brain trauma, thermal stress, and neurodegenerative diseases, e.g., Alzheimer's disease [7,10,11]. Ischemia and hypothermic stress may lead to a heat-shock-like response [12]. As a central component of chaperons' intracellular network, heat shock protein 70 (Hsp70) is a neuroprotective factor involved in assisting protein folding, translocation, and degradation [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothermia was shown to be neuroprotective in neonatal hypoxic injury (Azzopardi 2014). An animal study showed that Hsp70 combined with valproic acid (HDAC inhibitor) and therapeutic hypothermia resulted in neuroprotection in a rat asphyxial cardiac arrest model (Oh et al 2021). In human adults there is controversy with both positive and negative outcomes with moderate hypothermia.…”
Section: Introductionmentioning
confidence: 99%
“…Hypothermia was shown to be neuroprotective in neonatal hypoxic injury (Azzopardi et al 2014 ). An animal study showed that Hsp70 combined with valproic acid (HDAC inhibitor) and therapeutic hypothermia resulted in neuroprotection in a rat asphyxia cardiac arrest model (Oh et al 2021 ). In human adults, there is controversy with both positive and negative outcomes with moderate hypothermia.…”
Section: Introductionmentioning
confidence: 99%